BALANCE ANALYSIS OF WATER DISPENSER ASSEMBLY LINE USING RANKED POSITIONAL WEIGHT, REGION APPROACH, AND LARGEST CANDIDATE RULE METHODS AT PT. XYZ - Mohammad Rachman Waluyo; Nur Fajriah (Prosiding Seminar Nasional Waluyo Jatmiko, 2026)
XYZis one of the largest electronic goods manufacturers in Indonesia, producing various electronic products, including water dispensers. Based on the performance graph over the past six months, the efficiency rate of the assembly line was below the company’s standard, and several workstations experienced bottlenecks. Therefore, an analysis of the water dispenser assembly line balancing was conducted to meet the company’s performance standards. To support this analysis, data sufficiency testing, data uniformity testing, and standard time calculations in the assembly process were performed. The line balancing was then analyzed using the Ranked Positional Weight, Region Approach, and Largest Candidate Rule methods. The results showed that the actual line efficiency reached 121.41%, with a balance delay of -21.41%, indicating a significant number of bottleneck workstations, initially totaling 14. After analysis using the three methods, line efficiency increased to 80.9%, and balance delay improved to 19.1%. Regarding the smoothness index, the Ranked Positional Weight and Largest Candidate Rule methods yielded 145.715 seconds, while the Region Approach produced 145.790 seconds, with an increased total of 21 workstations. Furthermore, a simulation using Arena software and a Paired Samples T-Test yielded a significance value of 0.317, confirming that the simulation model passed verification and validation.